Trimethylamine stimulated and dissolved organic matter inhibited methane production in sediment from the Poyang Lake, China. Issue 20 (17th October 2016) - Wang, Jiajia; Liu, Chunying; Gong, Xiaofeng; Liu, Yuanmu; Chen, Chunli
ABSTRACT: Methane (CH4 ) emitted from wetlands contributes significantly to the greenhouse effect. The Poyang Lake, the largest freshwater lake in China, is fed by five rivers and connects to the Yangtze River. The area of the lake fluctuates dramatically between drawdown and flood periods with large areas of wetlands. In order to understand the CH4 production capacity and factors that influence CH4 production in the wetland, a static closed chamber combined with a gas chromatograph technique was used to investigate the influence of substrates and electron acceptors on methanogenesis. The results showed that CH4 production capacity of sediments from the Poyang Lake was and it was stimulated by trimethylamine (TMA) to a great extent. Incubation temperature played a vital role on CH4 production in sediments and the optimum temperature for methanogenesis was 35°C. Minimum CH4 production capacity occurred with the addition of FeCl3, and the inhibitory effects of electron acceptors decreased in the sequence: FeCl3 > MnO2 > DOM > Fe2 O3 . In this study, DOM was demonstrated as one of the inhibitors to methanogenesis and TMA was the main substrate of methanogens in the sediments of the Poyang Lake whose pH value is 7.83.